GAYA KEPEMIMPINAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PEGAWAI DINAS SOSIAL PROVINSI MALUKU UTARA - Fatmawaty Fatmawaty; Abdullah Wajir Jabid; Abdurrahman Jannang; Rahmat Sabuhari (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the influence of transformational leadership and path goals on organizational citizenship behavior (OCB). The approach used is quantitative research. The population was obtained from all civil servants of the Social Service of North Maluku Province, and 134 respondents were used as research samples. The data analysis technique used in is regression analysis using Smart-PLS as a statistical test tool. The results of this research show that leadership style has a positive and significant effect on OCB. This empirical fact provides an explanation that leaders must be able to maintain and improve transformational and path-goal leadership styles in carrying out activities as institution leaders in the workplace, which have a significant impact on OCB. Future research could add happiness at work and organizational culture as independent variables with a broader unit of analysis.